1998
DOI: 10.1017/s0022377898006734
|View full text |Cite
|
Sign up to set email alerts
|

Review and present status of the TEXTOR radiative improved (RI) mode

Abstract: From 1990, the boronized TEXTOR tokamak was characterized by an improved confinement (coined the ‘I mode’) at high power that was substantially better than the L mode, but densities had to be limited to n[bar]e0/nGR[lsim ]0.5–0.6, where nGR is the Greenwald density limit. With the injection of Ne, Si or Ar in order to increase the edge radiation and provided that γ=Prad/Ptot[greater, similar]0.5, PNBI-co/Ptot[greater, similar]0.25 and n[bar]e0/nGR[greater, similar]0.75, a further improved co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…The turbulent particle flux convected power is 20% that of the radiated power in L mode conditions (37% radiated power) and drops to 1% of the radiated power in RI mode conditions (95% radiated power); thus the particle confinement does not play a critical direct role in the energy exhaust. Not only τ p but also τ E shows a sharp increase with radiated fraction [48], showing a good correlation between the increase in energy and particle confinement and indicating that the mechanism responsible for the enhancement affects both the particle and the energy confinement. The τ E /τ p ratio exhibits a tendency to increase with density in RI mode discharges, as shown in Fig.…”
Section: Particle and Energy Confinementmentioning
confidence: 71%
“…The turbulent particle flux convected power is 20% that of the radiated power in L mode conditions (37% radiated power) and drops to 1% of the radiated power in RI mode conditions (95% radiated power); thus the particle confinement does not play a critical direct role in the energy exhaust. Not only τ p but also τ E shows a sharp increase with radiated fraction [48], showing a good correlation between the increase in energy and particle confinement and indicating that the mechanism responsible for the enhancement affects both the particle and the energy confinement. The τ E /τ p ratio exhibits a tendency to increase with density in RI mode discharges, as shown in Fig.…”
Section: Particle and Energy Confinementmentioning
confidence: 71%
“…confinement [3]. The application of radiofrequency (RF) heating during the current ramp up phase of a plasma produces a reverse shear (RS) in the Q profile and an increase in confinement [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other important issues are magnetic shear as well as flow shear. In general, it is found that the addition of non-locality tends to stabilize ITG modes (Hahm and Tang 1989;Hong and Horton 1990;Hong et al 1991;Bai et al 1998;Vandenplas et al 1998;Waltz et al 1998;Tokar et al 1999). In view of the potentially negative effect that the ITG instability might have on core confinement, it is important to note that effects not considered in the usual analysis often tend to stabilize the ion-temperature-gradient mode.…”
Section: Introductionmentioning
confidence: 99%